UJI KOSENTRASI PUPUK ORGANIK CAIR DAN AB MIX TERHADAP PERTUMBUHAN PAKCOY ( BRASSICA RAPA L. ) METODE HIDROPONIK WICK: Kata kunci: Pakcoy, POC Intanpari, AB Mix - Heru Muladi Heru; Dewi Ratna Nuhayati; Siswadi Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2022)
Concentration iTest iof iLiquid iOrganic Fertilizei and AB iMix ion thei Growthi ofi Pacoyi (Brassica rapa L.) Wick Hydroponic Method. Thisi researchi wasi conductedi ati thei Experimentali Gardeni ofi thei Facultyi ofi Agriculture, Slameti Riyadii Universityi, Surakartai, Jl. Jaya Wijaya No. 384 Ex. Banjarsari. district. Banjarsari, Surakarta City, Central Java, in December 2021 – January 2022. Thisi studyi aimed toi determinei thei effecti ofi various doses ofi POC Intanpari and ABi Mixi on thei growthi ofi Pakcoyi plantsi using the Wick hydroponic method. Thisi studyi isi a factoriali experimenti consistingi ofi twoi factors arranged according toi ai Completelyi Randomizedi Designi (CRD). iThe treatmenti is as follows: the first factor is Organic Fertilizer Intanpari 5 cc / L, Organic Fertilizer Intanpari 10 cc / L, Organic Fertilizer Intanpari 15 cc / L, the second factor is Control Without AB Mix ( 0 ), Nutrition AB Mix 2.5 cc / L, Nutrition AB Mix 5 cc / L, Nutrition AB Mix 7.5 cc / L. Thus there were 12 treatment combinations with 3 replications, so 36 experimental units were obtained. Parameter datai werei analyzedi using analysisi iof variancei (ANOVA) andi continued iwith ithe iBNT itest iwith a ilevel iof 5%. iBased ion iPOC ithe iresults iof ithe iresearch, iand discussion, it cani be iiconcluded iithat: ( 1 ) Giving POC Intanpari gave an effect on the for observing the fresh weight of roots, but had no effect on the for observing plant height, number of leaves, root length, plant wet weight and plant dry weight. (2) The application of AB Mix nutrition had an effect on the observed of plant height and plant wet weight, but had no effect on the observation, number of leaves, root length, root fresh weight and plant dry weight. ( 3 ) The interaction between the concentration of POC Intanpari and nutrient AB Mix had an effect on observations, number of leaves and fresh weight of roots, but had no effect on observations, plant height, root length, planti wet iweight, iand iplant dry iweighti.